2018
DOI: 10.1038/s41467-018-03352-3
|View full text |Cite
|
Sign up to set email alerts
|

Drought drives rapid shifts in tropical rainforest soil biogeochemistry and greenhouse gas emissions

Abstract: Climate change models predict more frequent and severe droughts in the humid tropics. How drought will impact tropical forest carbon and greenhouse gas dynamics is poorly understood. Here we report the effects of the severe 2015 Caribbean drought on soil moisture, oxygen, phosphorus (P), and greenhouse gas emissions in a humid tropical forest in Puerto Rico. Drought significantly decreases inorganic P concentrations, an element commonly limiting to net primary productivity in tropical forests, and significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
163
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(170 citation statements)
references
References 66 publications
5
163
1
1
Order By: Relevance
“…At TSP forest, soils in the groundwater discharge zone emit on average 7,000 μg CH 4 -C·m −2 ·hr −1 (Figure 3), which is within the range of global averages for wetland CH 4 emissions (Turetsky et al, 2014). However, this CH 4 emission is higher than the values reported for riparian soils in temperate (Itoh et al, 2009;Kaiser et al, 2018;Warner et al, 2018) and tropical forests (O'Connell et al, 2018). This may be related to the high groundwater tables during monsoonal summer at our site (Figure 2d).…”
Section: Journal Of Geophysical Research: Biogeosciencessupporting
confidence: 61%
“…At TSP forest, soils in the groundwater discharge zone emit on average 7,000 μg CH 4 -C·m −2 ·hr −1 (Figure 3), which is within the range of global averages for wetland CH 4 emissions (Turetsky et al, 2014). However, this CH 4 emission is higher than the values reported for riparian soils in temperate (Itoh et al, 2009;Kaiser et al, 2018;Warner et al, 2018) and tropical forests (O'Connell et al, 2018). This may be related to the high groundwater tables during monsoonal summer at our site (Figure 2d).…”
Section: Journal Of Geophysical Research: Biogeosciencessupporting
confidence: 61%
“…Drought conditions during our study greatly decreased soil moisture and changed typical topographic patterns in soil moisture and O 2 availability across hillslopes at our research site. Several previous studies have found lower soil O 2 levels, higher soil moisture, and higher N gas fluxes in valley compared to ridge and slope locations at our experimental sites (O'Connell et al, 2018;Silver et al, 1999;Silver et al, 2013). However, at a site adjacent to ours during the drought, valley positions had the largest percentage increase in O 2 availability, with concentrations increasing from~5% prior to the drought to~15% in June (O'Connell et al, 2018).…”
Section: 1029/2018jg004851mentioning
confidence: 43%
“…However, at a site adjacent to ours during the drought, valley positions had the largest percentage increase in O 2 availability, with concentrations increasing from ~5% prior to the drought to ~15% in June (O'Connell et al, ). This shift put valley soils in the range of O 2 conditions typical of ridge and slope soils in this landscape (O'Connell et al, ; Silver et al, ). Our data show similarly anomalous soil moisture patterns across topographic positions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the dry season, the trend observed by Singh et al (1997) was reversed, with CH 4 consumption stimulated by additional moisture. The study described here was performed in a tropical wet forest more similar to a subtropical wet forest (O'Connell et al, 2018), than a dry tropical forest (Singh et al, 1997); however, in this site the drought experienced during the El Niño of 2015-2016 was an extreme negative precipitation anomaly, and the observed increased in methane consumption was dramatically different from all other dates studied.…”
Section: Journal Of Geophysical Research: Biogeosciencesmentioning
confidence: 98%